Sengketa Perjanjian Jual Beli Tanah Dalam Perkembangan Hukum Perjanjian Nasional: Perspektif Hakim - Jafar Chan; Fauzie Yusuf Hasibuan (Postgraduate of Jayabaya University, 2015)
This research about the discovery of the law by the judge as stipulated in the rulings, particularly in the purchase agreement of land dispute has spawned some of the rules of law as well as annotation of the dedsion which not only applies to the parties that the litigants,but the rule of law and annotations such decision has contributed to the development of na- tional contract law. This research using descriptive analytic conceptual approach for the rule of law is derived from the discovery of the law by judges and the rule of law was raised surface and serve as the rule of law which further guidance in terms of buying and selling land, espedally customary land.Implementation of the discovery of the law by the judge has given a positive contribution to the development of national legal development, particularly for the development of contract law that con- tinues to evolve with the dynamic development of sodety. Keywords: Purchase agreement, discovery of the law, national contract law